Implementation of Cognitive Assessment of Physics Subjects at SMAN 10 Makassar - Muhammad Yusuf; Kaharuddin Arafah; Bunga Dara Amin (Universitas Muhammadiyah Makassar, 2020)
This study aims to find factual data regarding the implementation of cognitive assessments in physics learning in the Makassar 10th Middle School. To achieve this goal, research has been carried out using a qualitative paradigm. The focus of the study was on cognitive assessments conducted by subjects at the 10th high school physics teacher in Makassar. Data were collected using questionnaires, documentation, observation, and interview techniques. The four techniques were carried out back and forth throughout the study until the data was saturated. To check the validity of the data used source triangulation techniques. The data obtained were then analyzed using the Miles and Huberman technique, which consisted of data reduction, data display, and conclusion drawing. The results showed that the implementation of cognitive assessment in physics subjects in Makassar 10 public high schools had run but was not optimal. Assessment tools have been prepared by the teacher well. In conducting the assessment, the teacher does not appear to be fully consistent in carrying out cognitive assessments as previously prepared. Giving questions is made by the teacher spontaneously, sometimes taking questions from textbooks or the internet.